Scout stop: Museum showcases personal collection of memoralilia Todd Wildermuth - Wildermuth, Todd (Raton, NM Raton Range, 1999)
Newspaper article on the museum showcasing a personal collection of Dennis Downing.
Master list item #: 144
File location is in the Raton file Cabinet
Keywords: Downing, Dennis; Maggio, Kevivn; Downing, Susan; Scouting musuem; Amtrak; Philmont Scout Ranch; Local History; Biography; Life and Customs; Boy scout museum; Boy scout; Cub Scout; Patches; Memorabilia collection; Southwest jewelry; Raton, New Mexico; Cimarron, New Mexico; Colfax County; Deming, New Mexico; Tacoma, Washington; Colorado Springs, Colorado